2017
DOI: 10.1177/1934578x1701200319
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Flavonoids from Asteriscus Maritimus

Abstract: One new flavonol glycoside, patuletin-7-O-[6-O-caffeoyl-2-O-[(S)-3-hydroxyisobutanoyl]glucopyranoside] (astermaritimoside) (1) and four known flavonoids, patuletin-7-O-β-[-6-O-[(S)-3-hydroxyisobutanoyl]glucopyranoside] (2), patuletin-7-O-[6-O-caffeoylglucopyranoside] (3), patuletin-7-O-β-Dglucopyranoside (4) and quercetin-3-O-β-rutinoside (5) have been isolated from Asteriscus maritimus (L.) Less. Chemical structures were elucidated by mass spectrometric, and 1 H NMR, 13 C NMR, COSY, HMQC and HMBC spectroscopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In Tanzania, B. pinnatum and C. limon are used to treat respiratory diseases of bacterial origin (Innocent et al, 2022). The works of Daroui-Mokaddem (2012) showed that organic extracts of E. globulus also possess essential oils, compounds with pronounced antibiotic and anti-inflammatory activities such as robustaol A, robustadials and eucalyptol. Antiinflammatory activities have been revealed in the essential oils of C. schweinfurthii (Mathouet et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In Tanzania, B. pinnatum and C. limon are used to treat respiratory diseases of bacterial origin (Innocent et al, 2022). The works of Daroui-Mokaddem (2012) showed that organic extracts of E. globulus also possess essential oils, compounds with pronounced antibiotic and anti-inflammatory activities such as robustaol A, robustadials and eucalyptol. Antiinflammatory activities have been revealed in the essential oils of C. schweinfurthii (Mathouet et al, 2020).…”
Section: Discussionmentioning
confidence: 99%